Oral benzo[a]pyrene administration attenuates dextran sulfate sodium-induced colitis in mice. (1st February 2022) - Adachi, Keita; Ishizawa, Michiyasu; Uno, Shigeyuki; Kubota, Hitomi; Henmi, Takuo; Koshinaga, Tsugumichi; Makishima, Makoto; Sakurai, Kenichi
Abstract: Benzo[ a ]pyrene (BaP) is an environmental pollutant produced by combustion processes and is present in grilled foods as well as in tobacco smoke. BaP acts as an agonist for the aryl hydrocarbon receptor (AHR), and is metabolized by AHR-inducing enzymes. BaP metabolism can result in either detoxification or metabolic activation, the latter leads to an increased risk of disease, particularly lung cancer and cardiovascular disease, in a context-dependent manner. Although AHR activation has been thought to protect against inflammatory bowel disease, it remains unknown whether BaP exerts a protective or deleterious effect on colitis. In this study, we examined the effect of oral BaP administration on colitis induced by dextran sulfate sodium (DSS) in mice, an animal model of inflammatory bowel disease. BaP administration attenuated weight loss, shortening of the colon, disease activity index scores, and histological damage in DSS-induced colitis mice. BaP also suppressed colonic expression of inflammation-associated genes and plasma interleukin-6 secretion induced by DSS treatment. BaP-DNA adduct formation, a marker of BaP metabolic activation, was not enhanced in the colon after DSS treatment. Thus, oral BaP exerts an anti-inflammatory effect on DSS-induced colitis, without the toxicity associated with metabolic activation. The results provide insights into the disease-specific roles of BaP. Highlights: Benzo[ a ]pyrene (BaP) is known to activate AHR and be metabolically activated. Oral BaP attenuates dextran sulfate sodium-induced colitis in mice. BaP suppresses inflammation-related gene expression in the intestine of colitis mice. Oral BaP administration does not induce toxicity related to its metabolic activation. Oral BaP exerts a tissue-selective protective effect against colitis.